Analysis of Customer Decision Determinants in Choosing Small Medium Enterprise Products at Bank Muamalat - Kumalasari, Marta Della; Rizal, Fitra (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: This study aims to determine the effect of customer perceptions, motivation, and knowledge on choosing products for small and medium enterprises, either partially or simultaneously. Research Methods: This type of research is quantitative. The population in this study were all customers who chose small and medium enterprises products at Bank Muamalat KCP Ponorogo, totaling 395 customers. Withdrawal of samples using incidental techniques with solving measurements, so 80 respondents were obtained. Methods of data collection through questionnaires. Test results using SPSS 23. Results: The results of this study indicate that the variables of perception, motivation, and customer knowledge significantly affect the decision to choose products for small and medium enterprises at Bank Muamalat KCP Ponorogo both partially and simultaneously. Conclusion: This study concludes that for customer perception, motivation, and knowledge, if it increases, it will also increase customer decisions in choosing small and medium enterprise products at Bank Muamalat KCP Ponorogo.